IDENTIFICATION OF VOLATILE FLAVOUR COMPOUNDS OF HOKI (Macruronus novaezelandiae) AND ORANGE ROUGHY (Hoplostethus atlanticus) OILS - Hari Eko Irianto; Carmen C. Fernandez; G. J. Shaw (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Identification of volatile flavour compounds of hoki (Macruronus novaezelandiae) and orange roughy (Hoplostethus atlanticus) oils has been carried out.  Flavour compounds were extracted by a purging system and collected using a porous polymer Tenax TA trap.  The gas chromatography-mass spectrometry (GC-MS) was used to identify the volatile flavour compounds.  The predominant compounds contributing to the volatile flavour of hoki oil were methyl ethyl benzoate, ethyl benzoate and 1,1-dimethylethyl-2-propionic acid.  Meanwhile, the main volatile flavour components of orange roughy oil were toluene, cyclohexane, 1,1-dimethylethyl-2-methyl propionic acid and tetrachloroethane.